Prolonged Grief Disorder and the Cultural Crisis - Stelzer, Eva-Maria; Zhou, Ningning; Maercker, Andreas; O’Connor, Mary-Frances; Killikelly, Clare (Frontiers in Psychology, 2020)
Prolonged grief disorder (PGD) is included as a new mental health disorder in the 11th edition of the International Classification of Diseases (ICD-11). Understandably, this has boosted research efforts to investigate this newcomer to psychopathology. However, the use of different diagnostic algorithms has resulted in substantially different prevalence rates both within and across cultural groups. Furthermore, global applicability of the new criteria outside of the Global North has not been yet been established. This perspective presents key findings from Asian research groups and discusses the roadblocks to unified PGD research, including the heterogeneric use of diagnostic algorithms and the lack of cultural compatibility of ICD-11 items. The authors discuss the key issues and address implications for practice.